Determining the acceptable level of physician compliance with a treat‐to‐target strategy in early rheumatoid arthritis. (22nd December 2015) - Wabe, Nasir; Sorich, Michael J.; Wechalekar, Mihir D.; Cleland, Leslie G.; McWilliams, Leah; Lee, Anita; Spargo, Llewellyn; Metcalf, Robert; Hall, Cindy; Proudman, Susanna M.; Wiese, Michael D.
Abstract: Objective: To determine the minimum cut‐points for rate of physician compliance with a treat‐to‐target (T2T) strategy needed to achieve optimal rates of remission or low disease activity (LDA). Method: In this analysis of longitudinal observational data from patients with early RA, physician compliance with a T2T treatment protocol was determined for each clinic visit over 3 years. Remission and LDA were measured by Disease Activity Score in 28 joints (DAS28), simplified disease activity index (SDAI) and clinical disease activity index (CDAI). The minimum physician compliance rates for predicting these outcomes were calculated using receiver operating characteristic (ROC) curves. Result: Overall, 149 patients completed 3078 clinic visits over 3 years of follow‐up. Treatment decisions complied with the T2T protocol in 2343 of these visits (76.1%). The minimum cut‐points for physician compliance rates that predicted remission and LDA according to DAS28 were 81.1% and 70.7%, respectively, and to predict remission and LDA according to SDAI, the respective cut‐points were 92.7% and 77.4%. Based on these cut‐points, three categories of physician compliance with T2T were proposed: high (to maximize the likelihood of achieving remission, > 80% according to DAS28 or > 90% according to SDAI/CDAI); medium (the minimal physician compliance to achieve LDA, 70–79% according to DAS28 or 75–89% for SDAI/CDAI); and low (< 70% for DAS28 and < 75% for SDAI/CDAI), where remission and LDA are unlikely). When patients were stratified by baseline disease activity, the physician compliance rate cut‐points were similar for most outcomes at year 3. Conclusion: Using real‐life clinical data, we determined the thresholds for physician compliance with a T2T strategy that stratified patients according to their disease outcomes and proposed a system for classifying physician compliance as high, medium and low.